Challenges and Opportunities of Resource-Aware Allocation Frameworks for Big data tools in Cloud Computing - Rengasamy, R; Chidambaram, M (International Journal of Computer Sciences and Engineering, 2018)
System virtualization is the backbone of Cloud computing has been liberalizing its services to distributed dataintensive platforms such as MapReduce and Hadoop. Cloud computing empowers consumers to access online resources using the internet, from anywhere at any time without considering the underlying hardware, technical management and maintenance problems of the original resources. Cloud services are obtained from data centres which are distributed throughout the world. Big Data Applications with resource aware allocation has become an active research area in last three years. The Hadoop framework has been adopted to work efficiently in cloud computing. System virtualization is the backbone of Cloud computing, has been liberalizing its services to distributed data-intensive platforms such as MapReduce and Hadoop. Cloud computing empowers consumers to access online resources using the internet, from anywhere at any time without considering the underlying hardware, technical management and maintenance problems of the original resources.We present a detail study of various resource allocation and other scheduling challenges as well as frameworks for Hadoop Jobs in Cloud Computing.